2021
DOI: 10.1002/curj.103
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences of a first‐year block model curriculum in higher education

Abstract: The first year in Higher Education (HE) is an international priority because of its importance to the retention of students. While initiatives to improve students’ commencing experience continue to develop one area that has received limited consideration is the first‐year curriculum. The aim of the research reported in this paper was to enhance the student experience in HE by expanding understandings of the first‐year curriculum. Focus groups and an online questionnaire were the research methods used to, explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Immersive scheduling has been successfully implemented in HE institutions in the United Kingdom, Canada, and the United States of America; there are now two Australian universities moving all units and courses into immersive models (McKie, 2022). As noted previously, studies from these contexts indicate that immersive formats can enhance the academic performance of diverse student cohorts (see Austin & Gustafson, 2006;Loton et al, 2022;Turner et al, 2021) by reducing cognitive load (Richmond et al, 2015;Scott, 2003) and engaging students in active learning (Ambler et al, 2021;Lee & Horsfall, 2010;Scott, 2003). However, despite these generally positive findings, there is little research exploring how specific curriculum features drive achievement improvements in immersive learning.…”
Section: Research Gap and Questionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Immersive scheduling has been successfully implemented in HE institutions in the United Kingdom, Canada, and the United States of America; there are now two Australian universities moving all units and courses into immersive models (McKie, 2022). As noted previously, studies from these contexts indicate that immersive formats can enhance the academic performance of diverse student cohorts (see Austin & Gustafson, 2006;Loton et al, 2022;Turner et al, 2021) by reducing cognitive load (Richmond et al, 2015;Scott, 2003) and engaging students in active learning (Ambler et al, 2021;Lee & Horsfall, 2010;Scott, 2003). However, despite these generally positive findings, there is little research exploring how specific curriculum features drive achievement improvements in immersive learning.…”
Section: Research Gap and Questionsmentioning
confidence: 85%
“…Notwithstanding these positive findings, evidence also suggests that to facilitate such outcomes, immersive scheduling models should involve the careful implementation of active learning pedagogy (Ambler et al, 2021;Lee & Horsfall, 2010;Scott, 2003). Founded in constructivist learning theory, active learning requires students to participate and evaluate, rather than passively consume information (Biggs, 1999;Michael, 2006).…”
Section: Literature Review Immersive Active Learning and Student Achi...mentioning
confidence: 99%
“…It is widely held, for instance, that teaching large groups makes creating a sense of personalisation in the classroom much harder, meaning that catering to a variety of learning needs can be overlooked (Ambler et al, 2021). Interactivity in the form of facilitating participatory moments in the classroom is also made more difficult at scale, and maintaining consistency amongst cohorts that are large enough to necessitate multiple teaching staff can be equally hard to ensure (Babcock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In facilitating the exploration of different teaching styles, block teaching can subsequently cater to diverse learning preferences, which is often a difficulty in largescale teaching contexts. In doing so, it enhances the student learning experience, which has been shown to improve overall engagement (Ambler et al, 2021). This is not the least because the nature of block teaching introduces an element of flexibility.…”
Section: Scaling-up Intensive Deliverymentioning
confidence: 98%
“…An extensive number of articles have been published in scholarly journals, such as the Canadian Journal of Higher Education (CJHE), and cover similar iii areas of higher education research. Much of the research about retention has focused on the first-year experience, especially regarding large lecture courses (Ahadi et al, 2019;Ambler et al, 2021;Browne & Perrier, 2015;Hauck et al, 2020;Goodman & Pascarella, 2006;van der Zanden et al, 2018). This research has demonstrated the importance of strong supports for incoming students transitioning from the relatively small classes of secondary school to the large, introductory classes in lecture halls that might hold as many people as entire secondary schools.…”
Section: Historical and Current Research In Higher Educationmentioning
confidence: 99%